Analisis Persepsi Masyarakat Terhadap Aplikasi JAKI (Jakarta Kini) di Provinsi DKI Jakarta - Prasetia, I Putu Sawitra Danda; Wijaya, Komang Adi Sastra; Yudartha, I Putu Dharmanu; Savitri, Renny (Jayapangus Press, 2024)
This research aims to analyze and obtain an overview of public perceptions of the JAKI application as an innovative public service platform in DKI Jakarta which is implemented by BLUD Jakarta Smart City. This type of research is descriptive qualitative. Research data is secondary data obtained through data collection in the comment column in the Google Play Store rating and review feature. The data analysis used in this research is of Nvivo 14 software. The research results showed three things, namely the first related to history, a brief overview, and the features available in the JAKI application. Second, regarding data on the number of downloaders and active users of the JAKI application. And the third is related to the public's perception of active users of the JAKI application. It was found that the public's perception of the JAKI application as a comprehensive, innovative service platform tends to be negative. This is shown by three of the four e-service quality indicators receiving negative perceptions. Only one indicator received a positive perception. Apart from that, the findings also show that the sentiment raised is dominated by negative sentiment regarding the JAKI application.